The Social Science Learning Effectivity in a Post-Pandemic through Active Learning Method at Al-Ma’arif Junior High School in Jombang 2022 - Bashith, Abdul; Asnawan, Asnawan (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
Since the World Health Organization (WHO) designated the novel coronavirus disease (Covid-19) a pandemic, a significant proportion of activities across all domains of life have encountered challenges, including those pertaining to education. The Indonesian learning process is confronted with a series of alterations that require the ingenuity of educational institutions to mitigate the consequences of the pandemic caused by the novel coronavirus (Covid-19). One of the most efficacious methods is the implementation of active learning. The objective of this paper is to identify the types of active learning methods that can be employed, the active learning process itself, and the outcomes of active learning. The focus of this paper is Al-Ma’arif Junior High School, situated in Jombang-Jember. It can thus be concluded that the active learning methods implemented are group discussion, social observation, inductive learning, contextual, presentation, problem-solving, and demonstration. Furthermore, the active learning process is comprised of three stages: planning, implementation, and evaluation. Finally, the results of this method are evidenced by the development of students’ abilities in the cognitive, affective, and psychomotor domains.